Abdominophrenic Dyssynergia: A Narrative Review. (30th September 2022) - Damianos, John A.; Tomar, Sanjeevani K.; Azpiroz, Fernando; Barba, Elizabeth
Abstract : Chronic bloating and abdominal distension are common and highly bothersome gastrointestinal symptoms. Although the differential diagnoses for bloating and distension are broad, these symptoms are frequently associated with disorders of the gut-brain interaction. Functional abdominal bloating may be a result of visceral hypersensitivity, whereas abdominal distension seems to be a somatic behavioral response associated with abdominophrenic dyssynergia, featuring diaphragmatic contraction and abdominal wall relaxation. We review the available literature regarding abdominophrenic dyssynergia and comment on its epidemiology, diagnosis, treatment, and avenues to address in the near future.